1996
DOI: 10.1002/ana.410390418
|View full text |Cite
|
Sign up to set email alerts
|

T Cell–mediated ganglionitis associated with acute sensory neuronopathy

Abstract: A 67-year-old man presented with acute painful sensory loss, areflexia, ataxia, urinary retention, and severe constipation and became unable to walk within 2 weeks. He died suddenly 5 weeks after the onset of symptoms. Autopsy revealed widespread inflammation of sensory and autonomic ganglia with immunocytochemical evidence of a CD8+ T cell-mediated cytotoxic attack against ganglion neurons. This observation suggests a novel pathogenetic mechanism of immune-mediated human ganglion cell damage comparable to mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…In human idiopathic SN, both T cell-mediated immune response and autoantibody against spinal ganglion neurons were involved on its pathogenesis [1,9,16,18]. However, a previous report of human acute SN [10] described that CD8 positive-T cell-mediated immunity against ganglion neurons might mostly contribute the pathologic events and humoral immunity had only a limited role. Some forms of human SN have been associated with lung or breast cancers called as "paraneoplastic syndromesh" [7,9].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In human idiopathic SN, both T cell-mediated immune response and autoantibody against spinal ganglion neurons were involved on its pathogenesis [1,9,16,18]. However, a previous report of human acute SN [10] described that CD8 positive-T cell-mediated immunity against ganglion neurons might mostly contribute the pathologic events and humoral immunity had only a limited role. Some forms of human SN have been associated with lung or breast cancers called as "paraneoplastic syndromesh" [7,9].…”
Section: Discussionmentioning
confidence: 98%
“…Regardless of whether the distal peripheral nerve lesions are primary or secondary changes, the lesions have clinical utility for the diagnosis using biopsy of the distal peripheral sensory nerves. In fact, biopsy specimens of the sural nerve mostly consisting of sensory nerves have been used for pathological evaluations of acute SN in humans [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…This has been pathologically demonstrated with paraneoplastic SNN (Graus et al ., 1990; Dalmau et al ., 1991; Wanschitz et al ., 1997), HIV infection (Scaravilli et al ., 1992; Esiri et al ., 1993), Sjögren's syndrome, unclassified connective diseases and rare idiopathic cases (Okajima et al ., 1983; Sobue et al ., 1988; Griffin et al ., 1990; Hainfellner et al ., 1996; Kurokawa et al ., 1998; Colli et al ., 2008). Interestingly, in all of these circumstances, dorsal root ganglia degeneration was associated with an inflammatory T-cell reaction suggesting that the disorder is mainly driven by a cell-mediated immune response.…”
Section: Introductionmentioning
confidence: 99%
“…20 In fact, pathologic studies in SSN have confirmed the site of pathology by demonstrating inflammation and cellular loss in the dorsal root ganglia, which are thought to reflect the immune-mediated inflammatory process causing the syndrome. 12,17,21 In a few cases, autopsy studies in patients with paraneoplastic SSN have also revealed degeneration of the posterior columns of the spinal cord, suggesting that inflammation is not limited to the peripheral sensory nerves, and the central nervous system may also be involved. 13 However, radiographic evidence (e.g., MRI) of central nervous system involvement in SSN has not been reported.…”
Section: Discussionmentioning
confidence: 99%